A Novel Paramagnetic Nanoparticle T2 Magnetic Resonance Imaging Contrast Agent With High Colloidal Stability: Polyacrylic Acid‐Coated Ultrafine Dysprosium Oxide Nanoparticles. (7th August 2020) - Marasini, Shanti; Yue, Huan; Ho, Son Long; Cha, Hyunsil; Park, Ji Ae; Jung, Ki‐Hye; Ghazanfari, Adibehalsadat; Ahmad, Mohammad Yaseen; Liu, Shuwen; Chae, Kwon‐Seok; Chang, Yongmin; Lee, Gang Ho
Abstract : Until now, there have been limited studies on T2 magnetic resonance imaging (MRI) contrast agents (CAs) using paramagnetic nanoparticles (NPs). In this study, ultrafine dysprosium oxide (Dy2 O3 ) NPs were synthesized as a T2 MRI CA. To obtain high biocompatibility and colloidal stability in aqueous medium for in vivo applications, they were grafted with polyacrylic acid. They displayed paramagnetism with an appreciable magnetization value at 300 K and consequently, an appreciable transverse water proton spin relaxivity (r2 ) value which increased as the applied MR field increased. Their potential as a T2 MRI CA was proved by taking in vivo T2 MR images in mice. Abstract : PAA‐coated Dy2 O3 nanoparticle, an aqueous nanoparticle suspension sample, an HRTEM image showing nanoparticles (labeled as dotted circles), T2 MR images before and 30 min after intravenous injection of the nanoparticle suspension sample showing negative contrast enhancements at the liver (labeled as dotted lines).